SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KELAYAKAN PENERIMA BANTUAN UMKM MENGGUNAKAN HYBRID ENTROPY-WEIGHTED PRODUCT : DECISION SUPPORT SYSTEM FOR DETERMINING THE ELIGIBILITY OF MSME AID RECIPIENTS USING A HYBRID ENTROPY–WEIGHTED PRODUCT METHOD - Rizky Prima; Agus Sidiq Purnomo (LPPM Universitas Abdurrab, 2026)
The process of determining the eligibility of Micro, Small, and Medium Enterprises (MSME) aid recipients in Joint Business Groups (KUBE) is still often done manually, making it prone to subjectivity and inaccuracy. This study aims to develop a Decision Support System (DSS) that can objectively evaluate the eligibility of MSME aid recipients using the hybrid Entropy-Weighted Product method. The Entropy method is used for objective criteria weighting based on data variation, while the Weighted Product method is used for alternative ranking. The research data consists of 22 members of KUBE Bareng Mulyo with five assessment criteria: monthly turnover, market access, length of business, number of workers, and legality. The system was developed using PHP programming language with MySQL database following the Turban model. The results show that the Entropy method produces the highest weight on the criteria of length of business (45.58%) and number of workers (28.36%), indicating these two criteria as the most significant differentiating factors. The ranking results show Endang Sri Rejeki as the first rank with a preference value of 0.1043, which is consistent with actual field conditions. The developed system can improve transparency and objectivity in the selection of MSME aid recipients.